Windows Phone 7 Made Simple - Made Simple Learning, MSL; Westfall, Jon (Apress : Imprint: Apress, 2011)
With Windows Phone 7, Microsoft has created a completely new smartphone operating system that focuses on allowing users to be productive with their smartphone in new ways, while offering seamless integration and use of Microsoft Office Mobile as well as other productivity apps available in the Microsoft App Store. Windows Phone 7 Made Simple offers a clear, visual, step-by-step approach to using your Windows Phone 7 smartphone, no matter what the manufacturer. Author Jon Westfall is an expert in mobile devices, recognized by Microsoft as a "Most Valuable Professional" with experience teaching both businesses and consumers. This book will get you started with the basics and then teach you tricks and shortcuts that will save you time and help you maximize your productivity.